UPAYA MENINGKATKAN AKTIVITAS BELAJAR DAN KETERAMPILAN MENULIS KARANGAN NARASI SISWA KELAS VIII MELALUI MODEL PEMBELAJARAN PROBLEM SOLVING DI SMP NEGERI 1 SALING - Sepriani, Yessi; Missriani; Muhammad Ali (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2026)
The purpose of this study is to describe the process of improving learning activities and narrative writing skills of eighth grade students through the problem solver learning model at SMP Negeri 1 Saling, Empat Lawang Regency. This study was motivated by the low learning activities and narrative writing skills of students, where the average score of students ranged from 55-68, still below the Minimum Completion Criteria (KKM) set at 70. The method used was Classroom Action Research (CAR) which was implemented in three cycles. Each cycle consisted of planning, action implementation, observation, and reflection. The subjects of the study were 30 eighth grade students of SMP Negeri 1 Saling. Data collection was carried out through observation of learning activities and narrative writing skills tests. Data were analyzed descriptively qualitatively and quantitatively. The findings of the study showed a significant increase in each cycle. In cycle 1, only 23.3% of students actively participated in learning with an average writing skill score of 66.97 and classical completeness of 40%. In cycle 2, active activity increased to 70% with an average score of 76.53 and a completion rate of 70%. In cycle 3, active activity reached 93.3% with an average score of 87.10 and a classical completion rate of 93.33%, exceeding the 85% success indicator. This research was limited to one class and one school, so generalization of the findings requires caution. The practical implication of this research is that the problem-solving learning model can be used as an effective alternative strategy for teaching narrative writing at the junior high school level. Socially, this implementation model contributes to improving the quality of Indonesian language learning and empowering students to think critically and creatively. The original value of this research lies in the systematic application of the problem-solving model in three CAR cycles to simultaneously improve two variables: learning activities and narrative writing skills in a regional junior high school context. Keywords: Learning Activities; Writing Skills; Narrative Writing; Problem-Solving Learning; Classroom Action Research.